Changes in Major and Trace Element Concentrations in Low-Rank Coal after Hydrogen Peroxide Pre-treatment: A Screening Approach Based on Enrichment Index - Yulia Jamastuti; Shofa Rijalul Haq; Rika Ernawati; Hendriono Hendriono (Journal of Earth and Marine Technology (JEMT), 2026)
Low-rank coal contains minerals and associated major and trace elements that may be mobilized during processing, particularly under pre-treatment and leaching conditions. This study aimed to characterize the major and trace elements in low-rank coal, evaluate their relative enrichment in solid residues following hydrogen peroxide (H₂O₂) pre-treatment, and assess the potential implications of mobile Fe and Mn for groundwater quality. Elemental concentrations before and after pre-treatment were determined using Inductively Coupled Plasma Mass Spectrometry (ICP-MS), while changes in elemental abundance were evaluated using an enrichment index (Δ%). The untreated coal contained a range of major and trace elements, including Fe, Mn, Yb, Er, Zn, Co, Ni, Mg, Al, Sc, Li, Na, Ga, and Ce. H₂O₂ pre-treatment altered the distribution of several elements in the solid residue, with Fe and Mn showing the most pronounced relative enrichment. These changes are likely associated with the oxidation and transformation of metal-bearing mineral phases under oxidative conditions, whereas other elements exhibited variable responses depending on their modes of occurrence and mineral associations. Leachate analysis by Atomic Absorption Spectroscopy (AAS) further confirmed the mobilization of Fe and Mn into the aqueous phase. Mn concentrations remained below the Indonesian mining wastewater standard (Permen LHK No. 5/2022), whereas Fe concentrations exceeded the regulatory limit in the 40- and 60-mesh samples. In addition, the leachates remained acidic, with pH values below 6. These findings indicate that oxidative pre-treatment can influence both elemental redistribution in coal residues and metal mobility into the aqueous phase, highlighting the importance of controlling pre-treatment conditions and neutralizing acidic leachates prior to discharge. Overall, the proposed screening approach provides a practical preliminary framework for assessing the geochemical mobility of elements in low-rank coal.